Adaptive Fuzzy Sliding Mode Control for Hydraulic Servo System of Parallel Robot - Fenglan Jia; Li Hou; Yongqiao Wei; Yunxia You; Lili Yan (Institute of Advanced Engineering and Science, 2014)
The hydraulic servo control system, which is the important component of parallel robot, is a high order, nonlinear, dynamic asymmetry, parameter uncertain system, which seriously affect dynamic performance of robot, so it is very difficult to gain good performance with traditional control. Based on sliding mode variable structure control method combined with fuzzy control and adaptive control, an adaptive fuzzy sliding mode control algorithm was presented by taking the Stewart platform servo control system of parallel robot as the research object, and the uncertain term of the sliding mode controller was approximated with adaptive fuzzy control method. The simulation results showed that compared with the conventional PID control applied to the same hydraulic control system, the new controller has a strong robustness, good traceability with regard to model uncertainties, unknown external disturbances and changes in the operation conditions, as well as much better adaptive characteristics. The simulation results also showed that the adaptive fuzzy sliding mode control system can solve the dynamic asymmetrical performance and poor stability of parallel robot, and can greatly improve the robot control precision. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5087